MULTICULTURAL MENTALITY CONSTRUCTION IN ISLAMIC EDUCATION AT INDONESIAN ISLAMIC BOARDING SCHOOL - Amirul Mu’minin (Universitas Islam Malang, 2021)
This discussion is related to the construction of the multicultural metality of santri, especially orphaned and elderly students, starting from how orphaned and elderly students are educated to be able to get a strong mentality, also how they are educated to accept religious diversity and respect each other. This research is a case study type field research with a qualitative approach. This approach is used because the data will be taken directly from interviews to the main source, observations at research locations, observations on events, and tracing of documents which are all narrated and decrypted to obtain comprehensive understanding The mental form of Islamic boarding school students' mental education sources of Allah's religion (SPMAA) Turi Lamongan, among others: religious (righteous), patient, knowledgeable (pious), trustworthy (trustworthy), inviting goodness (da'wah), balancing between the world and the afterlife, tolerant, and openness that make students become human beings who religiousize and humanize humans.Keywords: construction, multicultural mentality, Islamic boardingschool